HISTOLOGICAL AND HISTOCHEMICAL CHANGES IN THE BRONCHIAL TREE OF THE LUNGS OF WHITE LABORATORY RATS UNDER CONDITIONS OF CHRONIC ENDOGENOUS NEOPLASTIC INTOXICATION - Rymar, A.A.; Nebesna, Z.M.; Ohinska, N.V.; Kulbitska, V.V.; Hetmanyuk, I.B.; Lisnychuk, N.Ye. (World of Medicine and Biology, 2024)
Histological changes in the bronchi of rats with colorectal cancer include both: direct lesions due to metastasis and side effects from chronic intoxication and inflammatory processes. Such changes can significantly impair lung function and require appropriate therapy to alleviate the condition. Microscopically, it was found that under conditions of experimental oncogenesis in the lungs of experimental animals significant destructive and degenerative changes in the walls of large, medium and small bronchi were found, characterized by alteration of the mucosal epithelium with its detachment into the lumen bronchi, proliferation of lymphocytes and their accumulation in the form of large conglomerates in the wall. Immune function disorders were characterized by hyperplasia of peribronchial lymphoid tissue throughout the bronchial wall, with thinning of the epithelium up to its destruction. There was a remodeling of components of the ground substance and fibers with a predominance of sulfated glycosaminoglycans and the formation of bronchial wall fibrosis.
Keywords: lungs; bronchi; histological and histochemical changes; experimental carcinogenesis; endogenous intoxication